Secular governance and religious diversity in Western, Central, Eastern Europe, and Latin America: Comparative challenges and emerging models - Peralta, Eric (Society and Economy in Central and Eastern Europe, 2026)
Europe and Latin America navigate religious pluralism through contrasting secular frameworks shaped by distinct historical trajectories. This analysis examines how Latin American secular states manage religious diversity differently from Western, Central, and Eastern Europe. Despite secularization theories predicting religious decline, both regions show religions maintaining public influence while states remain formally neutral. Migration, technology, and evangelical movements create region-specific challenges: Latin America faces growth in evangelical Christianity and indigenous revitalization; Europe confronts Islamic integration and Christian nationalism. The emerging frame-work of pluriconfessional secularization, in which secular states accommodate diverse religious traditions without privileging any denomination while religious institutions adapt to democratic frameworks, offers analytical tools beyond traditional secularization paradigms. This study provides strategies for managing religious diversity in interconnected societies.